2015
DOI: 10.1093/cercor/bhv278
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Findings in Female-to-Male Transsexuals: Testing a New Hypothesis

Abstract: MRI of functional connectivity, cortical thickness, surface area, and gray matter volume was carried out in 28 female-to-male transsexuals (FtM-TR) and 68 cis-sexual controls (34 male). FtM-TR displayed thicker mid-frontal, precuneal-parietal, and lingual cortex than both male and female controls, whereas, in regions with reported anatomical sex differences among the controls, FtM-TR followed patterns of the gender assigned at their birth. FtM-TR also displayed weaker functional connections from the pregenual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
107
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(125 citation statements)
references
References 64 publications
15
107
1
1
Order By: Relevance
“…This accords with our structural MRI studies of GD (Manzouri et al 2015; Savic and Arver 2011), as well as studies of white matter microstructure (Kranz et al 2014), graph theoretical network analyses of white matter connectivity (Hahn et al 2015), and resting state functional connectivity (Lin et al 2014), all of which also suggest that GD may be associated with its own, singular features. In the latter resting state fMRI study, MtF and FtM as a group, compared with controls, demonstrated greater degree connectivity of the postcentral gyrus and superior parietal lobule (“body representation areas”) within a whole brain network, and greater connectivity of these nodes with sensorimotor network nodes.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This accords with our structural MRI studies of GD (Manzouri et al 2015; Savic and Arver 2011), as well as studies of white matter microstructure (Kranz et al 2014), graph theoretical network analyses of white matter connectivity (Hahn et al 2015), and resting state functional connectivity (Lin et al 2014), all of which also suggest that GD may be associated with its own, singular features. In the latter resting state fMRI study, MtF and FtM as a group, compared with controls, demonstrated greater degree connectivity of the postcentral gyrus and superior parietal lobule (“body representation areas”) within a whole brain network, and greater connectivity of these nodes with sensorimotor network nodes.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, our recent study of cortical thickness in a (partially overlapping)sample of GD individuals demonstrated significantly thicker cortex in the ACC, mPFC, precuneus, cuneus, left inferior parietal, and temporal cortex in FtM than both male and female controls (Manzouri et al 2015). In the absence of longitudinal data it is, however, not feasible to disentangle between the two alternatives, which, in addition, are not necessarily mutually exclusive.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results suggest a heightened focus on sensory input in body representation. Manzouri, Kosidou, and Savic (2015) showed differences in the “own-body image network” and suggested that FtM individuals may have weaker connections between body perception networks and body self-ownership networks. They also reported reduced functional connectivity between the amygdala and the right precuneus and temporo-parietal junction, right extrastriate body area, and the fusiform cortex that might reflect greater separation of body perception and body-related emotion.…”
Section: Introductionmentioning
confidence: 99%